About the new approach to building algorithms and processes to predict earthquakes by statistical model - Lư, Ngô Thị; Phương, Trần Việt (Vietnam Journal of Earth Sciences, 2013)
A new approach to to building algorithms and processes to predict earthquakes by statistical model is presented in this paper.The essence of this method is based on the idea about the concept of the set of earthquakes with sources in a certain subregion S in the form of time series of random parameters (time at earthquake sources Ti, magnitude of the earthquake  Mi,  with random intervals between them D ti).The task of the statistical model is predicted  the time (Ti) of the earthquake in region S and it’s intensity (magnitude Mi). In this case the time Ti of prediction earthquake and its magnitude Mi are considered random events.The prediction task time Ti of earthquake and its magnitude Mi just is problem for determination of the mathematical expectation and the confidence interval  of them with probability Pg ensure the accuracy of forecasts.This approach not only allows to determine the accuracy of the forecast results, but also allow to determine the time and magnitude of the predicted events. Applying this method in combination with other approaches that have physical characteristics will enhancing effective  research earthquake prediction in Vietnam.